Photoinduced 1, 2-dicarbofunctionalization of alkenes with organotrifluoroborate nucleophiles via radical/polar crossover. Issue 26 (11th June 2021) - Cabrera-Afonso, María Jesús; Sookezian, Anasheh; Badir, Shorouk O.; El Khatib, Mirna; Molander, Gary A.
Abstract : Alkene 1, 2-dicarbofunctionalizations increase molecular complexity. Herein, the carboallylation, carboalkenylation, carboalkynylation, and carboarylation of olefins is accomplished through radical/polar crossover with organotrifluoroborates. Abstract : Alkene 1, 2-dicarbofunctionalizations are highly sought-after transformations as they enable a rapid increase of molecular complexity in one synthetic step. Traditionally, these conjunctive couplings proceed through the intermediacy of alkylmetal species susceptible to deleterious pathways including β-hydride elimination and protodemetalation. Herein, an intermolecular 1, 2-dicarbofunctionalization using alkyl N -(acyloxy)phthalimide redox-active esters as radical progenitors and organotrifluoroborates as carbon-centered nucleophiles is reported. This redox-neutral, multicomponent reaction is postulated to proceed through photochemical radical/polar crossover to afford a key carbocation species that undergoes subsequent trapping with organoboron nucleophiles to accomplish the carboallylation, carboalkenylation, carboalkynylation, and carboarylation of alkenes with regio- and chemoselective control. The mechanistic intricacies of this difunctionalization were elucidated through Stern–Volmer quenching studies, photochemical quantum yield measurements, and trapping experiments of radical and ionic intermediates.